Associations Among Trajectories of Sleep Disturbance, Depressive Symptomology and 24-Hour Urinary Cortisol in HIV+ Women Following a Stress Management Intervention. Issue 5 (3rd September 2019) - McIntosh, Roger; Antoni, Michael; Seay, Julia; Fletcher, Mary Ann; Ironson, Gail; Klimas, Nancy; Kumar, Mahendra; Schneiderman, Neil
ABSTRACT: Objective : The burden of sleep disturbance and depressive symptomology is high for persons living with HIV and particularly so for women. While cognitive behavioral stress management (CBSM) is shown to reduce symptoms of depression and 24-hr urinary free cortisol output (CORT) in HIV+ men, less is known about the effects of CBSM on mood and concomitant sleep disturbance in HIV+ women. The study aim is to model longitudinal change in sleep disturbance, depressive symptomology, and CORT for HIV+ women exposed to a 12-week CBSM intervention or control condition. Methods : Self-reported sleep quality and depressive symptomology, along with CORT, was collected from surveys at baseline and approximately every three months thereafter for nine months from 130 HIV+ women (Mage  = 38.44, SD  = 7.73). The data was used to specify a parallel process latent growth model with CORT as a time-varying covariate. Results : The model showed acceptable fit. There was a linear decline in sleep disturbance (β = −0.32, p  < .05) and logarithmic decline in depressive symptomology (β = −0.33, p  < .05) for those receiving the intervention. Decline in sleep disturbance predicted lower CORT at nine months. Furthermore, having less depressive symptoms at baseline was associated with lower initial levels of sleep disturbance and greater improvement in sleep quality over time. There was no discernible association between sleep and mood disturbance in the control group. Across groups, there was a consistent association between older age and greater sleep disturbance ( r  = 0.34, p  < .01). Conclusion : Sleep disturbance appears to be a behavioral target for CBSM in HIV+ women although older age, preintervention levels of depressive mood, and time-varying levels of CORT output may limit improvement in sleep quality over time.